Exploring trade practice and market before and after the advent of Islam in Arabia / Irfan Shahid - Shahid, Irfan (Universiti Teknologi MARA Selangor, 2018)
Trade and commerce is an integral part of human civilisation. Trade practice before the advent of Islam is a great concern for researchers and students of Islamic Business. It was based on injustice and dishonesty. Islam abolished these customs and propounded the modules based on justice and balance. This is a theoretical attempt to explore the nature and methods of trade prevalent in Arabia before the Islam. This paper also highlights some rulings of Islam made to govern the trade and market.